Asymmetric Discounting in Intertemporal Choice: A Query Theory Account - Weber, E. U. (Institutional Knowledge at Singapore Management University, 2007)
People are impatient and discount future rewards more when they are asked to delay consumption than when they are offered the chance to accelerate consumption. The three experiments reported here provide a process-level account for this asymmetry, with implications for designing decision environments that promote less impulsivity. In Experiment 1, a thought-listing procedure showed that people decompose discount valuation into two queries. Whether one considers delayed or accelerated receipt of a gift certificate influences the order in which memory is queried to support immediate versus delayed consumption, and the order of queries affects the relative number of patient versus impatient thoughts. Relative frequency and clustering of impatient thoughts predicts discounting and mediates the discounting asymmetry. Experiment 2 implicated query order causally: When participants listed reasons for immediate versus delayed consumption in the order used spontaneously in acceleration and delay decisions, the discounting asymmetry was replicated; reversing the order in which reasons were listed eliminated the asymmetry. The results of Experiment 3, which used an implicit-memory task, support a memory-interference account of the effect of query order.